The Ifluence of Knowledge,Religiosity, and Trust on Interest in Financing in Sharia Banking( Case Study on Halal MSME in Kediri Regency) - Kartika, Fitrotul Candra; Budianto, Eka Wahyu Hestya (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This study aims to measure the influence of knowledge, religiosity and trust on public interest in financing in Sharia Banking. This study uses quantitative methods by conducting interviews and distributing questionnaires to obtain data. The population in this study are people who have micro businesses that are or have applied for halal certification. In addition, the MSMEs studied were MSMEs that were conducting financing in Sharia Banking. As for selecting samples, researchers used convenience sampling techniques. The data analysis technique used to test this research uses multiple linear regression tests with the help of statistical aids, namely using the SPSS application. The results showed that knowledge, religiosity, and trust have a positive and significant influence on public interest, especially Halal MSMEs that do financing in Sharia Banking. The three variables also influence each other. indirectly and knowledge and religiosity affect a person's level of trust in the existence of sharia banking among the community.